Epidemiological profile of gestational syphilis in Northeast Brazil (Research, Society and Development, 2021)
The objective was to analyze sociodemographic and clinical data on gestational syphilis in northeastern Brazil. An ecological study, with a quantitative approach, based on secondary data from the Information System for Notifiable Diseases (SINAN), made available by the Information Technology Department of the Unified Health System (DATASUS) regarding cases of gestational syphilis in northeastern Brazil during the years from 2015 to 2019. There was an increase in the number of syphilis cases in pregnant women aged 20 to 29 years in all years analyzed (53.5%). Most pregnant women had incomplete 5th to 8th grade (23.3%), with a predominance of the brown race (68.6%). There was a significant increase in the number of cases over the period in the brazilians states, with the lowest growth in Paraíba (0.73%) and the highest in Bahia (1.91%). It could be noted that the incidence of gestational syphilis in young women has been increasing gradually in the Northeast, therefore, more effective interventions are needed to control the disease so that there is an increasingly reduction in cases of vertical and fetal complications.